OPERATION PARAMETERS OF MELT-SPINNING OF POLYPROPYLENE HOLLOW-FIBER MEMBRANES - KIM, JJ; HWANG, JR; KIM, UY; KIM, SS (ELSEVIER SCIENCE BV, 1995)
Microporous hollow fiber membranes were prepared via melt spinning of a polypropylene/soybean oil mixture. Many operation parameters of melt spinning process were examined in terms of the structure variation by scanning electron microscopy and bubble point pressure measurement. The initial composition of the melt solution affected the porosity and the pore size of the membrane. Melt viscosity of the hollow fiber spun depended on the spinning temperature and affected the structure. Increased melt-draw ratio enhanced the formation of the micropores and fibril structure. Subsequent cold-stretching of the hollow fiber membrane produced tiny fibrils and micropores via stretching and cleavage. A combination of thermally-induced phase separation and cold-stretching produced an unusually highly porous membrane without significant changes of the inside and outside diameters of the hollow fiber membranes.
Keywords: INDUCED PHASE-SEPARATION; POLYMER DILUENT SYSTEMS; THERMODYNAMICS